2017
DOI: 10.1016/j.ajhg.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide Association Study of Dupuytren Disease Reveals 17 Additional Variants Implicated in Fibrosis

Abstract: Individuals with Dupuytren disease (DD) are commonly seen by physicians and surgeons across multiple specialties. It is an increasingly common and disabling fibroproliferative disorder of the palmar fascia, which leads to flexion contractures of the digits, and is associated with other tissue-specific fibroses. DD affects between 5% and 25% of people of European descent and is the most common inherited disease of connective tissue. We undertook the largest GWAS to date in individuals with a surgically validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
123
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(137 citation statements)
references
References 59 publications
9
123
0
3
Order By: Relevance
“…Results from a GWAS of DD in UK Europeans (3,871 cases and 4,686 controls) were previously reported 4 . This GWAS summary data contained association statistics for 7,218,238 SNPs, with 6,991,033 SNPs that were imputed from individuals of European ancestry in the Haplotype Reference Consortium 19 .…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…Results from a GWAS of DD in UK Europeans (3,871 cases and 4,686 controls) were previously reported 4 . This GWAS summary data contained association statistics for 7,218,238 SNPs, with 6,991,033 SNPs that were imputed from individuals of European ancestry in the Haplotype Reference Consortium 19 .…”
Section: Methodsmentioning
confidence: 88%
“…Recent twin studies estimate the heritability (i.e., proportion of phenotypic variation explained by genetics) of DD to be ~80% 3 . The largest previous genome-wide association study (GWAS) of DD in individuals of European ancestry identified 26 genome-wide significant single-nucleotide polymorphism (SNP) associations in 24 independent risk regions 4 , and estimated the proportion of phenotypic variance attributable to additive effects of common variants (i.e., SNP-heritability) to be 0.53 4,5 . The vast majority (23 of 24) of DD associations lie in non-coding genomic regions with only one located in an intron 4 , thus the biological implications of these associations are not immediately clear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations